Premilinary Study in the Cause of Color in Zircon from Krông Năng Mining Area in Đắk Lắk Province - Vương, Bùi Thị Sinh; Hương, Lê Thị Thu (VNU Journal of Science: Earth and Environmental Sciences, 2015)
Zircon occurs in many colors including various shades of pink, red, purple, yellow, orange, brown as well as less common shades of green, and blue. Generally, the colors of zircon are caused by the trace element composition (transition metals, lanthanides, actinides and REEs) and radiation damage (radiation induced color centers) [1]. The color centers of zircon are complex and the details surrounding the color-inducing mechanisms are still debated. The authors collected some zircon samples from Krong Nang mining, Central Highlandss, using UV-Vis-NIR and FTIR techniques to determine the causes of their color. The UV-VIS-NIR absorption spectra of these samples show continuous increase absorption from around 600 nm toward the UV region occasionally with shoulder at around 500 nm, which are identified as structural defect color center due to the radiation damage by radioactive elements such as U and Th. The OH- hydrous species was detected in all FTIR absorption spectra confirm a slight radiation damage by radioactive elements of zircon samples. Keywords: Zircon, UV-Vis-NIR, FTIR.